A Multicomponent Strategy for the Regioselective Synthesis of [1, 3]‐Thiazinones from an Abundant Feedstock: Scope and Structural Elucidation. Issue 1 (5th December 2016) - Wadhwa, Preeti; Shube Hussen, Abdulkadir; Sharma, Anuj
Abstract: A novel and regioselective protocol for the synthesis of [1, 3]‐thiazinones via multicomponent reactions of readily available isothiocyanates, hydrazine monohydrate, aldehydes and dialkyl acetylenedicarboxylates is described. This approach exhibits operational simplicity, offering a new and expedient strategy for the direct synthesis of synthetically useful [1, 3]‐thiazinone compounds in good to excellent yields. The method could provide a low‐cost and environmentally benign alternative to currently employed methods. Moreover, unambiguous determination of the single product regioisomer through detailed 2D NMR spectroscopy, the scope and limitations of this environmentally friendly domino reaction are discussed. Abstract : A novel and regioselective protocol for the synthesis of [1, 3]‐thiazinones by multicomponent reactions of readily available isothiocyanates, hydrazine monohydrate, aldehydes and dialkyl acetylenedicarboxylates is described